Anxiety Profile of Parents and Teachers During the Pandemic COVID-19 At SDS. ST. Antonius VI Medan - Sinta Deslina; David M.T Simangunsong (Science Midwifery, 2021)
At the beginning of 2020, the world was shocked by a new incident, namely an outbreak of the corona virus disease. The spread of the infection is very fast every day and has spread to almost all parts of the world, including Indonesia. The government has implemented several steps so that the corona virus does not spread faster, such as work from home (WFH), social distancing, and others. This causes many people to feel anxious, panicked, and even stressed. The online learning system in schools also adds pressure to the community, which are teachers and parents of students. This results in an increase in the incidence of anxiety experienced by teachers and parents of students. The objective of the study was to know the description of anxiety in teachers and parents of students in SDS. St. Antonius VI Medan during the COVID-19 pandemic.This study used a descriptive research method with a cross sectional approach and sampling was carried out by using a total sampling technique. From 132 respondents, 63 people (48%) experienced anxiety and 69 people (52%) did not experience anxiety